2016
DOI: 10.1002/jmv.24464
|View full text |Cite
|
Sign up to set email alerts
|

Dengue severity associated with age and a new lineage of dengue virus‐type 2 during an outbreak in Rio De Janeiro, Brazil

Abstract: Dengue virus-type 2 (DENV-2) caused three outbreaks, in the years 1990, 1998, and 2008, in Rio de Janeiro, Brazil. The 2008 outbreak was the most severe in reported cases, hospitalizations, and deaths. To investigate virological and epidemiological factors that may have contributed to the pathogenic profile of 2008 epidemic, 102 patients sera obtained during the epidemic and inter-epidemic periods of three outbreaks were analysed by qRT-PCR to estimate viremia levels and their correlation with the clinical, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…Several reports have described an association of dengue severity with age . In this study, no significant differences were found in the incidence of DWWS between age groups (26.5% for <15 years vs 39.3% for >15 years; Table ), nor was there any significant correlation between the incidence of secondary infection and age groups (50.0% for <15 years vs 46.8% for >15 years; Table ).…”
Section: Resultsmentioning
confidence: 45%
See 3 more Smart Citations
“…Several reports have described an association of dengue severity with age . In this study, no significant differences were found in the incidence of DWWS between age groups (26.5% for <15 years vs 39.3% for >15 years; Table ), nor was there any significant correlation between the incidence of secondary infection and age groups (50.0% for <15 years vs 46.8% for >15 years; Table ).…”
Section: Resultsmentioning
confidence: 45%
“…Several reports have described an association of dengue severity with age. 6,7 In this study, no significant differences were found in the incidence of DWWS between age groups (26.5% for <15 years vs 39.3% for >15 years; Table 2), nor was there any significant correlation between the incidence of secondary infection and age groups (50.0% for <15 years vs 46.8% for >15 years; Table 2). Univariate and multivariate analyses revealed that patients over 15 years of age had a significantly increased risk of fever, retro-orbital pain, arthalgia, diarrhea, and thrombocytopenia compared to younger patients.…”
Section: Association Of Clinical Manifestations and Agementioning
confidence: 50%
See 2 more Smart Citations
“…First, we performed in silico analysis to further test the DENV‐host interactions related to the replication cycle in dendritic cells, the primary sentinel human target cell and the primary target for DENV replication and mediated immunity (Marovich et al., ; Schmid, Diamond, & Harris, ). We included DENV Serotype 2 strain 16681 in the in silico analysis (Figure ), which showed that DENV‐2 had a high abundance of predicted N ‐myristoylation sites and that DENV‐2 strains were associated with severe dengue cases and most frequently found in worldwide epidemics (Nunes et al., ; Wei & Li, ). DENV strain 16681 was isolated from a patient with a severe case of dengue fever and has been widely used to study DENV pathogenesis (Okamoto et al., ).…”
Section: Discussionmentioning
confidence: 99%